2019
DOI: 10.1063/1.5064804
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in linewidth quantification of overlapping Raman bands

Abstract: Spectral linewidths are used to assess a variety of physical properties, even as spectral overlap makes quantitative extraction difficult owing to uncertainty. Uncertainty, in turn, can be minimized with the choice of appropriate experimental conditions used in spectral collection. In response, we assess the experimental factors dictating uncertainty in the quantification of linewidth from a Raman experiment highlighting the comparative influence of (1) spectral resolution, (2) signal to noise, and (3) relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Other authors have shown through numerical models that the fitting uncertainty can be significantly smaller than the pixel width when that pixel/FWHM ratio is small and the system is well constrained. [65][66][67] The asymmetric peak broadening was evaluated by calculating the asymmetry factor, J, defined as the ratio of HWHM2 to HWHM1. An asymmetry factor of 1 indicates symmetric peak broadening.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have shown through numerical models that the fitting uncertainty can be significantly smaller than the pixel width when that pixel/FWHM ratio is small and the system is well constrained. [65][66][67] The asymmetric peak broadening was evaluated by calculating the asymmetry factor, J, defined as the ratio of HWHM2 to HWHM1. An asymmetry factor of 1 indicates symmetric peak broadening.…”
Section: Resultsmentioning
confidence: 99%
“…The common method for detecting overlap is visual inspection of the spectrum and of the peak fitting residuals. This depends on the spectral resolution of the equipment, the Raman background, and the signal-to-noise ratio (Saltonstall et al, 2019). Some investigators fitted overlapping peaks with two or more peak functions per Raman band (e.g., Geisler & Pidgeon, 2002;Kempe et al, 2018;Nasdala et al, 2002); this is however not useful for interpreting such fits in terms of radiation damage.…”
Section: Table 1 Radiation-damage Calibrationmentioning
confidence: 99%